Stem Cell Challenges in the Treatment of Neurodegenerative Disease - Feng, Zhongling (CNS Neurosci Ther, 2011)
Neurodegenerative diseases result from the gradual and progressive loss of neural cells and lead to nervous system dysfunction. The rapidly advancing stem cell field is providing attractive alternative options for fighting these diseases. Results have provided proof of principle that cell replacement can work in humans with Parkinson's disease (PD). However, three clinical studies of cell transplantation were published that found no net benefit, while patients in two of the studies developed dyskinesias that persisted despite reductions in treatment. Induced pluripotent stem cells (iPSC) have major potential advantages because patient‐specific neuroblasts are suitable for transplantation, avoid immune reactions, and can be produced without the use of human ES cells (hESC). Although iPSCs have not been successfully used in clinical trials for PD, patients with amyotrophic lateral sclerosis (ALS) were treated with autologous stem cells and, though they had some degree of decline one year after treatment, they were still improved compared with the preoperative period or without any drug therapy. In addition, neural stem cells (NSCs), via brain‐derived neurotrophic factor (BDNF), have been shown to ameliorate complex behavioral deficits associated with widespread Alzheimer's disease (AD) pathology in a transgenic mouse model of AD. So far, the FDA lists 18 clinical trials treating multiple sclerosis (MS), but most are in preliminary stages. This article serves as an overview of recent studies in stem cell and regenerative approaches to the above chronic neurodegenerative disorders. There are still many obstacles to the use of stem cells as a cure for neurodegenerative disease, especially because we still don't fully understand the true mechanisms of these diseases. However, there is hope in the potential of stem cells to help us learn and understand a great deal more about the mechanisms underlying these devastating neurodegenerative diseases.